The U.S. combat aircraft industry, 1909-2000 : structure, competition, innovation - Lorell, Mark A., 1947- (RAND, 2003)
In its FY02 Defense Appropriations Conference Report, Congress expressed concerns about reduced competition resulting in a decline in innovation in the U.S. fixed-wing military aircraft industry. Drawing on primary and secondary sources on the aircraft industry, this report provides a brief survey of industry structure, innovation, and competition in the U.S. fixed-wing combat aircraft industry from its earliest days to the present. It supports a much larger research effort that examines the future of the U.S. military aircraft industrial base in response to the above congressional concerns. The study suggests that it is possible to identify at least five distinct technology eras over the history of fixed-wing, heavier-than-air combat aircraft, each of which began with a period of revolutionary innovation, high rates of technology advancement, and significant improvement in performance. The historical evidence suggests, but does not prove, that an industrial structure that includes numerous prime contractors is conducive to encouraging the onset of periods of higher innovation when demand changes and market conditions are right. Without such an industry structure, new Defense Department initiatives may be necessary to promote high levels of innovation. This is a companion volume to a report on the future viability of the combat aircraft industry: Competition and Innovation in the U.S. Fixed-Wing Military Aircraft Industry (Santa Monica, Calif.: RAND, MR-1656-OSD, 2003) by John Birkler, Anthony G. Brower, Jeffrey A. Drezner, Gordon Lee, Mark Lorell, Giles Smith, Fred Timson, William P.G. Trimble, and Obaid Younossi. It should be of interest to members of Congress, congressional staff members, industry executives, and others in the civilian and uniformed defense policy community interested in the future viability of the U.S. military aircraft industrial base.